Israeli attacks wipe out entire families in Gaza - Amnesty International (Amnesty International, 2023)
Amnesty International has documented damning evidence of war crimes.
Israel
Keywords: 2023-10 October; Palestine

Social media companies must step up crisis response on Israel-Palestine as online hate and censorship proliferate - Amnesty International (Amnesty International, 2023)
Social media companies must urgently address the fanning of online hate and racism against Palestinian and Jewish communities, Amnesty International said as the conflict in Israel and the Occupied Palestinian Territories escalates further
Israel
Keywords: 2023-10 October; Palestine